Matching Faces with Emotional Expressions - Chen, Wenfeng; Lander, Karen; Liu, Chang Hong (Frontiers in Psychology, 2011)
There is some evidence that faces with a happy expression are recognized better than faces with other expressions. However, little is known about whether this happy face advantage also applies to perceptual face matching, and whether similar differences exist among other expressions. Using a sequential matching paradigm, we systematically compared the effects of seven basic facial expressions on identity recognition. Identity matching was quickest when a pair of faces had an identical happy/sad/neutral expression, poorer when they had a fearful/surprise/angry expression, and poorest when they had a disgust expression. Faces with a happy/sad/fear/surprise expression were matched faster than those with an anger/disgust expression when the second face in a pair had a neutral expression. These results demonstrate that effects of facial expression on identity recognition are not limited to happy faces when a learned face is immediately tested. The results suggest different influences of expression in perceptual matching and long-term recognition memory.